The world aluminum-bauxite market : - Woods, Douglas W. (Praeger, 1980)
This book introduce the world aluminum market before the IBA. Structure of the aluminum market. The aluminum market during world war II. The formation of the international. The international bauxite association and future developments in the aluminum market...